Integrating Soft And Hard Skills Through University Mentorship In Secondary Education: Integrasi Keterampilan Lunak Dan Keras Melalui Pendampingan Universitas Dalam Pendidikan Menengah - Amak Nasrul; Isnaini Rodiyah; Riska Amalia; Widaad Ariij Banafaj; Mutmaina (International Consortium of Education and Culture Research Studies, 2025)
General Background Global industrial competition necessitates a highly competent workforce equipped with comprehensive practical capabilities. Specific Background Within the Indonesian educational landscape, high schools frequently struggle to prepare learners for professional environments due to inadequate technological resources and pedagogical limitations. Knowledge Gap Although experiential learning theories advocate for practical assimilation, limited empirical understanding exists regarding how external mentorship programs specifically facilitate technical and interpersonal capability acquisition for high school learners. Aims This qualitative case study analyzes the implementation of an external mentorship initiative designed to develop learner capabilities at SMA Negeri 1 Tarik. Results In-depth interviews and participatory observations reveal that interpersonal competencies, including communication and leadership, are successfully assimilated into extracurricular projects, while technical proficiency in information technology is embedded within specific academic subjects. Furthermore, external mentors provide crucial operational support, although the initiative faces systemic barriers such as resource constraints, restricted digital access, and inadequate teacher training. Novelty This research uniquely identifies the dual-benefit mechanism where external mentors bridge institutional resource deficits while simultaneously acquiring practical teaching experience. Implications Educational stakeholders must prioritize comprehensive curriculum assimilation, stabilize technological infrastructure, and establish robust coordination between institutions to sustain optimal learner development. Highlights: Extracurricular activities and collaborative projects effectively cultivate essential interpersonal communication capabilities. Information technology application within academic subjects builds vital technical proficiencies for future professional readiness. Institutional resource limitations and digital access disparities remain significant barriers to optimal capability building. Keywords: Experiential Learning, Interpersonal Competenc, Technical Proficiency, Curriculum Development, Public Administration